Design of Rice Husk Rotary Dryer using Waste Heat Electrostatic Precipitator of The Cement Industry - ASTI DESI FITRIYANI; RATU FENNY MULDIANI; SRI WURYANTI (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2023)
ESP or electrostatic precipitator is a device used to capture particulate matter, such as dust, in exhaust gases using electrostatic principles. In the cement industry, ESP is commonly placed after the clinker cooler to clean the exhaust air from the cooling process, ensuring it is free from clinker dust. The clinker cooler is a device that cools down the clinker using air, reducing its temperature from an initial temperature of around 1450°C to approximately 100°C - 120°C. The exhaust air from the clinker cooler is then passed through the ESP at temperatures ranging from around 237°C to 311°C. Based on the temperature data, the exhaust air from the ESP has the potential for heat reuse for other processes, including as a heat source for drying rice husk, which is a common alternative fuel used in the cement industry and typically has a moisture content of around 25%-37%. The results of this design indicate that the exhaust heat from the ESP, with an input temperature of 275°C, is capable of drying rice straw pellets from a moisture content of 25% to 14.73% using a designed rotary dryer with a capacity of 21.6 t/h, a length of 41.58 m, and a diameter of 2.92 m. It is constructed using ASTM 283 C material with a thickness of 8.76 mm and is insulated with a 15.6 mm thick layer of aluminum foil